GAMBARAN RESILIENSI PADA LANSIA YANG TINGGAL DI PANTI PELAYANAN SOSIAL LANJUT USIA - Sh Sugiharto; Salisa Rahmawati (Universitas Karya Husada Semarang, 2024)
Unfortunate circumstances such as poverty, isolation, and neglect compel the elderly to reside in nursing facilities. In order to effectively cope with the various physical, psychological, social, and environmental changes that occur during the aging process, older individuals must possess the ability to adapt and demonstrate resilience. The study aims to provide a comprehensive description of the resilience levels exhibited by the elderly residents residing in the social welfare department-served nursing home. The present study employs a descriptive methodology with a cross-sectional approach. The study used total sampling to collect the samples. The study used Maneerat's Elderly Resilience Scale Questionnaire to measure resilience. The study applied univariate statistics, encompassing mean, standard deviation, and percentage, to the data. Out of a total of 49 respondents, 26 (53.1%) had strong resilience, whereas 23 (46.9%) had less resilience. Elderly people who live in a social welfare department-served nursing home tend to have good resilience. We anticipate that the nursing home's management will create programs that enhance resilience, such as problem-focused and emotionally-focused coping, as well as group activities that foster social and spiritual interaction among the elderly.